Elucidating the role of 4-hydroxy-2(3H)-benzoxazolone in chronic alcoholic liver disease via transcriptomics and metabolomics - Lu, Jun-Fei; Xing, Shang-Ping; Wei, Xia; Yang, Chun-Xia; Zhao, Gen-Shi; Ma, Xiao-Lin; Sun, Xue-Mei; Guo, Hong-Wei; Su, Zhi-Heng; Fang, Bin; Lin, Jun; Liu, Yan-Ying; et al. (Frontiers in Pharmacology, 2024)
Abstract BACKGROUND Chronic alcoholic liver disease (CALD) is a global health problem which includes multiple pathological processes such as immune inflammation and oxidative stress. 4-hydroxy-2(3H)-benzoxazolone (HBOA), an alkaloid isolated from Acanthus ilicifolius L, has been shown to exert hepatoprotective and immunomodulatory effects. However, its effects on CALD remain unclear. This study aimed to investigate the effects and underlying mechanisms of HBOA on CALD. METHODS Rats were administered alcohol by gavage continuously for 12 weeks to establish the CALD model, and then treated with HBOA by gavage for 4 weeks. Transcriptomics and metabolomics were used to predict the potential mechanisms of the effects of HBOA on CALD. Liver histology and function, oxidative stress, inflammatory cytokines, and the TLR4/NF-κB pathway components were evaluated. RESULTS HBOA significantly improved alcohol-induced liver injury and steatosis. It decreased the expression levels of pro-inflammatory cytokines (tumour necrosis factor-α [TNF-α], interleukin (IL)-1β, and IL-6), and increased the activities of antioxidant enzymes (superoxide dismutase [SOD], glutathione [GSH], and glutathione peroxidase [GSH-Px]). Western blotting confirmed that HBOA treatment largely diminished NF-κBp65 nuclear translocation. Comprehensive transcriptomics and metabolomics analyses indicated that HBOA regulated the glycerophospholipid metabolism pathway to achieve therapeutic effects in rats with CALD. CONCLUSION HBOA has a therapeutic effect on rats with CALD. Its mechanism of action mainly affects the glycerophospholipid metabolic pathway to promote lipid metabolism homeostasis by regulating the expression of Etnppl, Gpcpd1, and Pla2g4c. In addition, it may also inhibit the TLR4/NF-κB signaling pathway, thereby reducing the immune-inflammatory response.